1996
DOI: 10.1002/1361-6374(199606)4:2<93::aid-bio7>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent dot counting in interphase cell nuclei

Abstract: Fluorescence in situ hybridization allows the enumeration of chromosomal abnormalities in interphase cell nuclei. This process is called dot counting. To estimate the distribution of chromosomes per cell, a large number of cells have to be analysed, particularly when the frequency of aberrant cells is low. Automation of dot counting is desirable because manual counting is tedious, fatiguing, and time consuming. We have developed a completely automated fluorescence microscope system that counts fluorescent hybr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Several researchers have identified capability of the size and shape features to classify the cervix using the cytology image [ 72 , 73 , 75 ], FISH image [ 60 , 76 , 77 ], and electromagnetic spectrum [ 24 , 78 ]. Besides these features, the ratio of the same feature for different parts of a biological structure is used as another feature.…”
Section: Intelligent System Approach To Cervical Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…Several researchers have identified capability of the size and shape features to classify the cervix using the cytology image [ 72 , 73 , 75 ], FISH image [ 60 , 76 , 77 ], and electromagnetic spectrum [ 24 , 78 ]. Besides these features, the ratio of the same feature for different parts of a biological structure is used as another feature.…”
Section: Intelligent System Approach To Cervical Cancermentioning
confidence: 99%
“…For FISH image, the features from labeled biomarker spots of chromosomes 3 (red spot) and X (green spot) are the size of each colored spot [ 60 , 76 , 77 ], the effective radius of each red or green spot computed as the radius of a circle that had the same size as the colored spot [ 60 , 76 , 77 ], and the circularity of each colored spot [ 60 , 77 ].…”
Section: Intelligent System Approach To Cervical Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…These studies indicated a strong correlation of detection results between the manual methods and the semiautomated computer schemes. 19,20 Because the semiautomated methods require userintervention to exclude poorly segmented, overlapped, clustered, or nonepithelial cells and therefore are impractical in the clinical practice, some fully automated schemes have recently been developed and tested. These schemes usually include two processing and detection steps.…”
Section: Introductionmentioning
confidence: 99%